If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -30 = 56 + 4x Reorder the terms: -30 + 6x = 56 + 4x Solving -30 + 6x = 56 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -30 + 6x + -4x = 56 + 4x + -4x Combine like terms: 6x + -4x = 2x -30 + 2x = 56 + 4x + -4x Combine like terms: 4x + -4x = 0 -30 + 2x = 56 + 0 -30 + 2x = 56 Add '30' to each side of the equation. -30 + 30 + 2x = 56 + 30 Combine like terms: -30 + 30 = 0 0 + 2x = 56 + 30 2x = 56 + 30 Combine like terms: 56 + 30 = 86 2x = 86 Divide each side by '2'. x = 43 Simplifying x = 43
| -7-3v+11+12v=3(4v+5)-4(v+4) | | -8(b+5)=6(8+6b) | | f(x)=3x+4x^2 | | (5x+10)(7x-2)= | | -5x+6+6x=-3+7 | | 4x^2-x+3y-2=0 | | (4x^2)-7x-7=0 | | 29=7-2a | | 4x=3-ab | | 2(2x+7)=2x+20 | | 6x-17=23-9x | | -49=6c-13 | | 12-7=5-3 | | 3*(x+4)=2*(3-2x) | | 6x+2x+9x=17 | | 4(9n-3)+8n= | | 4x+ab=3 | | 9x*x-6x=1 | | -9(+-2)=-4(+-15) | | X(x+15)-4450=0 | | (-6i)(-6i)(-6i)= | | 3x-3=30x+6 | | 144=-2(7+8x) | | 3(x+10)+4(x+20)+5x=185 | | ab+4x=3 | | z^2=1-i | | (x^2)+10x+17=0 | | 3r^7t^7-6r^8t^6= | | 11x+14y=61979 | | x(9x-6)-1=0 | | 5(q+8)= | | 6(3k-8)=6(k-6) |